How to reduce Germany's current account surplus? - Jan Behringer; Till van Treeck; Achim Truger (Forum for a New Economy, 2020)
Germany has had a large and persistent current account surplus for the past almost two decades. We review different theoretical explanations of this phenomenon and conclude from the empirical litera-ture that Germany's external surplus reflects an imbalance that is a threat to macroeconomic stability at both the national and the international level. Interestingly, although intertemporal general equilibrium models highlight the role of private households in determining national current account positions, the increase in Germany's external balance for the most part is the reflection of larger financial balances of the corporate sector and the government. While the share of the national income going to the private household sector has declined dramatically since the early 2000s, the corresponding increase in the income share of the private corporate sector and the government was not accompanied by higher spending by these sectors on goods and services as a percentage of GDP. We discuss how the exter-nal surplus might be reduced through (a combination of) higher public and private demand for goods and services and shorter working hours.
Keywords: D31; D33; E21; F32; F41; 330; current account; external adjustment; sectoral balances; income distribution